Power and Politics in the Chinese Court System: The Enforcement of Civil Judgments - Clarke, Donald C. (Columbia Journal of Asian Law, 1996)
It is a staple of Chinese legal literature that the judgments of Chinese courts in civil and economic cases are plagued by a low execution rate and that this is a serious problem. This perception should be taken seriously. When the President of the Supreme People’s Court devotes significant space to it in his report to the National People’s Congress, as did Zheng Tianxiang in 1988′ and Ren Jianxin in subsequent reports, clearly something interesting is going on. Yet it would be a mistake to accept all reports uncritically. A critical examination of the claims and the evidence can yield a richer picture of reality than has been presented by the literature so far. The issue of whether court judgments can be enforced is important for a number of reasons, among which is its bearing on the relationship between the legal system and the economic system. Laws, courts, and court judgments are part of the institutional framework within which economic reform is being carried out in China. Obviously, the rules of the game have to change. But the move from a hierarchically administered economy to a primarily market economy means more than just changing the content of the rules. It implies a whole new way of rule-making and rule-enforcing.